A Linguistic Examination of the CapitalCube™ Market Effect Variables - Lusk, Edward J.; Halperin, Michael (Sciedu Press, 2016)
Introduction: Linguistic variables and the nuanced market information they afford are critical to the efficient and effective functioning of market trading platforms. In this research, we report on our investigation of the Linguistic Variables of the CapitalCube market navigation platform [CCMNP]. Study Précis: The focus of the study is to determine if there is directional meaning: {Neutral: Unfavorable: Favorable} implied by the unique Linguistic Qualifiers [LQ] attached to each set of Market Performance Variables [MPV] of the CCMNP. To this end, we collected these directional indications and linkages from a sample of Experts and also Informed & Trained Students. Results: We found that: (i) there was a high degree of agreement between the two rating groups respecting these directional indications for the LQ over the MPV, (ii) these directional rating results were differentiable from a random assignment, and (iii) there was general agreement relative to the directional indications respecting an a priori scoring given by two other experts. Impact: The LQ tested for the selected MPV of the CCMNP exhibited directional relevance, sensitivity, and specificity and therefore seem to be an intelligent set of linguistic descriptors enhancing the navigation acuity of the CapitalCube market navigation platform.
Keywords: Content Analysis; Directional Linguistic Acuity; Market Codex